HUBUNGAN ANTARA MINAT BELAJAR DENGAN PRESTASI BELAJAR PADA PELAJARAN PENDIDIKAN AGAMA ISLAM - Yal Robiyansyah; Egi Setiawan; Abdul Kodir; Tia Putri Pratiwi (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2023)
This research aims to determine the relationship between interest in learning and learning achievement in Islamic Religious Education subjects at SMK Informatika Bina Generasi 2 Bogor for the 2023/2024 academic year. This research is a type of quantitative research. Data collection techniques using questionnaires and documentation. The population in this study were students in Classes X and XI with a total of 133 students. The sample in this study consisted of 100 respondents. This sampling technique uses purposive sampling, the collection technique of which is based on certain considerations. Data analysis was tested using correlation analysis, validity, reliability, linear regression, and hypothesis testing. The results of the research show that there is a relationship between interest in learning and student achievement in Islamic Religious Education subjects. After carrying out a simple linear regression test, the value obtained from the formula Y= a+bX = 66.478 + 0.234X means that student learning achievement in Islamic religious education subjects is worth 66.478. The regression coefficient value of student interest in learning is 0.234. Apart from that, there is a significant relationship between interest in learning and PAI learning achievement at SMK Informatika Bina Generasi 2 Bogor, obtained rcount of 0.440 > rtable 0.195, while the Determination Coefficient contributes 19.4% to variable Y (Learning Achievement) in PAI subjects. The remaining 80.6% of student learning achievement is influenced by other factors. From the results of the research conducted, it was concluded that there is a significant relationship between interest in learning and student learning achievement.